EFFECT OF TAX AVOIDANCE ON FIRM VALUE OF SELECTED QUOTED COMPANIES NIGERIA (Journal of the Management Sciences, 2024)
The effect of tax evasion on firm value was investigated in the study. 177 companies that are quoted on the Nigerian Exchange Group are included in the study. Five companies made up the sample size. The study employed secondary sources for data collection. The dependent variable is the firms' value as determined by Tobin Q, whereas the independent variable, tax avoidance was measured with deferred tax, tax credit, dividend distribution, and employee benefit. The study's hypotheses were put to the test using the correlation coefficient. The research findings indicate that there is no statistically significant effect of deferred tax on firm value, nor is there any significant effect of tax credits on firm value. Additionally, there is a statistically significant effect of employee benefits on firm value. In order to avoid penalties for not remitting tax deductions, the study suggests that, management of companies plan their tax policies so as to avoid jeopardizing the firm's ability to generate profits; that companies always make an effort to remit their tax deductions to the appropriate tax authority; that companies look for other legal ways to increase their income and profit than to use tax avoidance strategies; and that firms always work with the tax authority to reduce their tax liability through tax incentives like tax abatement, tax holidays, subsidies.
Keywords: Deferred Tax, Dividend Payout, Employee Benefit, Firm Value, Tax Credit